Characterization of a Novel Creeping Tartary Buckwheat (Fagopyrum tataricum) Mutant lazy1 - Liang, Chenggang; Wei, Chunyu; Wang, Li; Guan, Zhixiu; Shi, Taoxiong; Huang, Juan; Li, Bin; Lu, Yang; Liu, Hui; Wang, Yan (Frontiers in Plant Science, 2022)
Gravity is known as an important environmental factor involved in the regulation of plant architecture. To identify genes related to the gravitropism of Tartary buckwheat, a creeping line was obtained and designated as lazy1 from the mutant bank by 60Co-γ ray radiation. Genetic analysis indicated that the creeping phenotype of lazy1 was attributed to a single recessive locus. As revealed by the horizontal and inverted suspension tests, lazy1 was completely lacking in shoot negative gravitropism. The creeping growth of lazy1 occurred at the early seedling stage, which could not be recovered by exogenous heteroauxin, hormodin, α-rhodofix, or gibberellin. Different from the well-organized and equivalent cell elongation of wild type (WT), lazy1 exhibited dilated, distorted, and abnormally arranged cells in the bending stem. However, no statistical difference of indole-3-acetic acid (IAA) levels was found between the far- and near-ground bending sides in lazy1, which suggests that the asymmetric cell elongation of lazy1 was not induced by auxin gradient. Whereas, lazy1 showed up-expressed gibberellin-regulated genes by quantitative real-time PCR (qRT-PCR) as well as significantly higher levels of gibberellin, suggesting that gibberellin might be partly involved in the regulation of creeping growth in lazy1. RNA sequencing (RNA-seq) identified a number of differentially expressed genes (DEGs) related to gravitropism at stages I (before bending), II (bending), and III (after bending) between WT and lazy1. Venn diagram indicated that only Pectate lyase 5 was down-expressed at stages I [Log2 fold change (Log2FC): −3.20], II (Log2FC: −4.97), and III (Log2FC: −1.23) in lazy1, compared with WT. Gene sequencing revealed that a fragment deletion occurred in the coding region of Pectate lyase 5, which induced the destruction of a pbH domain in Pectate lyase 5 of lazy1. qRT-PCR indicated that Pectate lyase 5 was extremely down-expressed in lazy1 at stage II (0.02-fold of WT). Meanwhile, lazy1 showed the affected expression of lignin- and cellulose-related genes and cumulatively abnormal levels of pectin, lignin, and cellulose. These results demonstrate the possibility that Pectate lyase 5 functions as the key gene that could mediate primary cell wall metabolism and get involved in the asymmetric cell elongation regulation of lazy1.